HIV, Immune Dysfunction, and the Natural History of Anal High-Risk Human Papillomavirus Infection in Gay and Bisexual Men. (21st November 2020) - Poynten, I Mary; Jin, Fengyi; Garland, Suzanne M; Hillman, Richard J; Molano, Monica; Roberts, Jennifer M; Templeton, David J; Phillips, Samuel; Law, Carmella; Fairley, Christopher K; Farnsworth, Annabelle; Grulich, Andrew E
Abstract: Background: Incidence of anal cancer is highest in gay and bisexual men (GBM). Better understanding of the natural history of anal high-risk human papillomavirus (hrHPV) infection is needed for anal cancer prevention. Methods: The Study of the Prevention of Anal Cancer was a 3-year study of Australian GBM, aged 35 years or older. We examined incidence, clearance, and risk factors for 13 hrHPV types at baseline and 3 annual visits. Results: In 525 men with ≥ 2 visits, 348 (66.3%) acquired ≥ 1 incident hrHPV infection. HPV16 incidence rates were similar, but non-16 hrHPV incidence was higher in HIV-positive (51.8/100 person years [PY]) than HIV-negative men (36.5/100 PY, P  < .001). Annual clearance rates of HPV16 (13.21/100 PY, 95% confidence interval, 10.53–16.56) were lower than for other hrHPV types. hrHPV clearance rates were not associated with HIV overall but were significantly lower in those with a lower nadir CD4 (<200 cells/µL) for HPV16 ( P  = .015) and other hrHPV types ( P  = .007). Conclusions: Higher incidence of non-16 hrHPV types, coupled with lower clearance of non-16 hrHPV types in those with past impaired immune function, is consistent with the greater role of non-16 hrHPV in anal cancer in HIV-positive people. Australia New Zealand Clinical Trials Registry: ANZCTR365383. Abstract : The incidence of infection with high-risk anal HPV other than HPV16 was higher among HIV-positive gay and bisexual men. Although not associated with HIV overall, hrHPV clearance was significantly lower in men with a nadir CD4 less than 200 cells/µL.